2018
DOI: 10.1021/acs.jpcb.8b00663
|View full text |Cite
|
Sign up to set email alerts
|

Cations Modulate Actin Bundle Mechanics, Assembly Dynamics, and Structure

Abstract: Actin bundles are key factors in the mechanical support and dynamic reorganization of the cytoskeleton. High concentrations of multivalent counterions promote bundle formation through electrostatic attraction between actin filaments that are negatively charged polyelectrolytes. In this study, we evaluate how physiologically relevant divalent cations affect the mechanical, dynamic, and structural properties of actin bundles. Using a combination of total internal reflection fluorescence microscopy, transmission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 46 publications
3
55
0
Order By: Relevance
“…Bundles of actin filaments are inherently stiffer than single filaments, such that a network of counterion-crossbridged filaments should have distinct mechanical properties from a network of single filaments [10]. For example, Mg 2+ concentrations of 10-50 mM have been reported to produce actin bundles with persistence lengths l p up to ∼4× larger than that of single actin filaments (l p ≈ 10 μm) [9,[11][12][13][14]. Further, theoretical studies have shown that the bending stiffness of a bundle is impacted by both the number of filaments comprising the bundle as well as the density of connections the bundle has with its neighbors, suggesting that both bundling as well as crosslinking of bundles may play an important role in the mechanics of counterion-crossbridged networks [5].…”
mentioning
confidence: 99%
“…Bundles of actin filaments are inherently stiffer than single filaments, such that a network of counterion-crossbridged filaments should have distinct mechanical properties from a network of single filaments [10]. For example, Mg 2+ concentrations of 10-50 mM have been reported to produce actin bundles with persistence lengths l p up to ∼4× larger than that of single actin filaments (l p ≈ 10 μm) [9,[11][12][13][14]. Further, theoretical studies have shown that the bending stiffness of a bundle is impacted by both the number of filaments comprising the bundle as well as the density of connections the bundle has with its neighbors, suggesting that both bundling as well as crosslinking of bundles may play an important role in the mechanics of counterion-crossbridged networks [5].…”
mentioning
confidence: 99%
“…Thus, we suggest a model for the mechanism by which Ca 2+ affects the assembly of FtsZ. The neutralization of the charges on the surface of the filaments by the counter ion-Ca 2+ could also be responsible for the bundling as suggested for the actin polymers [56,57]. 11).…”
Section: Paradoxical Effects Of Ca 2+ On the Assembly Of Ftsz Filamentsmentioning
confidence: 69%
“…During the initial stages of the assembly, the conformational change caused by Ca 2+ binding to FtsZ affects either the activation of monomers or the nucleation of the polymers by hindering the monomer-monomer association, as suggested above (Fig. It has been suggested that higher concentrations of divalent cations lead to the 'overcharge' on the filaments which perturbs the bundling [56,57]. The bundling of FtsZ filaments caused by Ca 2+ could be an independent effect where the conformational changes induced in FtsZ on binding to Ca 2+ , expose the residues or regions required for the lateral association [40].…”
Section: Paradoxical Effects Of Ca 2+ On the Assembly Of Ftsz Filamentsmentioning
confidence: 82%
See 2 more Smart Citations